Magneto-structural behaviour of Gd doped nanocrystalline Co-Zn ferrites governed by domain wall movement and spin rotations. Issue 17 (1st December 2018) - Mugutkar, Anil B.; Gore, Shyam K.; Mane, Rajaram S.; Batoo, Khalid M.; Adil, Syed F.; Jadhav, Santosh S.
Abstract: The rare earth gadolinium (Gd 3+ ) ions doped nanocrystalline cobalt-zinc ferrites chemically formulated as Co0.7 Zn0.3 Gdx Fe2-x O4 (x = 0–0.1) were synthetically prepared by sol-gel self-ignition process. The characterization the ferrite samples was performed by powder x-ray diffraction method. The analysis of x-ray diffractograms (XRD) reveals formation of cubic spinel phase without presence of any ambiguity peak. The calculated particle size of the samples varies between 18 nm and 28 nm showing decreasing trend with Gd 3+ doping. The distribution of cations analysed from XRD data propose occupancy of tetrahedral (A)-site by Zn 2+ and Fe 3+ while octahedral [B]-site by Fe 3+, Gd 3+ and Co 2+ ions. The morphology of the ferrites was studied from the SEM images. The nanocrystalline particles arranged in layers with presence of porous structure can be observed in the SEM images. The particles of spherical shape with mean diameter of 27 nm were observed in the TEM image. The confirmation of peaks revealed by XRD data was performed by SAED image of the ferrite. The fringe width of the lattice fringe in HRTEM confirms formation of pure spinel phase in the Gd 3+ doped Co-Zn ferrite. The VSM data analysed for measurement of magnetic parameters viz. coercivity, retentivity and saturation magnetization. The compositional variation of magnetization with Gd 3+ doping reveals spin canting due to non-collinearity of spins of (A) and [B]-site. The Y-K angles calculated from cation distribution data were increased with Gd 3+ doping due to spin canting. The variation of coercivity with Gd 3+ doping was in accordance with the variation of anisotropy constant. The frequency variation of real part (μ') and imaginary part (μ") of μ* (complex permeability) were studied as a function of Gd 3+ composition and frequency. The permeability was influenced by magnetic and structural parameters. The domain wall movement and spin rotations were responsible for magnetism in the ferrites.